A comparison of insertion methods for surgical placement of penetrating neural interfaces. (26th April 2021) - Thielen, Brianna; Meng, Ellis
Abstract: Many implantable electrode arrays exist for the purpose of stimulating or recording electrical activity in brain, spinal, or peripheral nerve tissue, however most of these devices are constructed from materials that are mechanically rigid. A growing body of evidence suggests that the chronic presence of these rigid probes in the neural tissue causes a significant immune response and glial encapsulation of the probes, which in turn leads to gradual increase in distance between the electrodes and surrounding neurons. In recording electrodes, the consequence is the loss of signal quality and, therefore, the inability to collect electrophysiological recordings long term. In stimulation electrodes, higher current injection is required to achieve a comparable response which can lead to tissue and electrode damage. To minimize the impact of the immune response, flexible neural probes constructed with softer materials have been developed. These flexible probes, however, are often not strong enough to be inserted on their own into the tissue, and instead fail via mechanical buckling of the shank under the force of insertion. Several strategies have been developed to allow the insertion of flexible probes while minimizing tissue damage. It is critical to keep these strategies in mind during probe design in order to ensure successful surgical placement. In this review, existing insertion strategies will be presented and evaluated with respect to surgical difficulty, immune response, ability to reach the target tissue, and overall limitations of the technique. Overall, the majority of these insertion techniques have only been evaluated for the insertion of a single probe and do not quantify the accuracy of probe placement. More work needs to be performed to evaluate and optimize insertion methods for accurate placement of devices and for devices with multiple probes.